Experimental test of a new dedicated natural gas engine - Masjuki, Haji Hassan; Kalam, Md. Abul; Ishak, A.; Khair, M.; Shahrir, A.; Yusof, A. (2009)
This paper presents experimental test results of a new compressed natural gas direct injection (CNG-DI) engine that has been developed from modification of a multi cylinder gasoline port injection (PI) engine. The major modifications done are (1) the injection system has been modified to gas direct injection using new high pressure gas injectors, (2) compression ratio has been changed from 10 to 14 through modification of piston and cylinder head, and (3) new spark plugs with long edge were used to ignite the CNG fuel. The CNG pressure at common rail was kept at 20 bar to be injected into engine cylinder. The engine has been operated with full throttle conditions to compare all the results with original base engine such as gasoline port injection engine and the CNG bi-fuel engine where the base engine has been converted to bi-fuel injection system to be operated with gasoline and CNG fuels. Hence, it can be mentioned that the original gasoline port injection engine has been modified to CNG bi-fuel and CNG-DI systems. The bifuel injection was developed using a gas conversion kit with gas port injection injectors. The test results obtained from CNG fuel using two different systems (i.e. bifuel and DI) will be investigated and compared with original gasoline engine. The test was conducted with computer controlled dynamometer to measure brake power, specific fuel consumption (SFC), exhaust emissions such as carbon monoxide (CO), oxides of nitrogen (NOx), and unburned hydrocarbon (HC). The objective of this investigation is to compare the test results between “CNG-DI”, with “CNG-BI” and “gasoline - PI” engines with the same displacement volume. It was found that the CNG-DI engine produces 4% higher brake power at 6000 rpm as compared to original gasoline fueled engine. The CNG-BI engine produces maximum power of 57 kW at 5500 rpm which is 23% lower than CNG-DI engine’s peak power (at 6000 rpm). The average BSFC of CNG-DI engine was 0.28% and 8% lower than gasoline-PI and CNG-BI engines respectively. The CNG-DI engine reduces 50% NOx emission as compared to base engine. However, the CNG-DI engine produces higher HC and CO emissions as compared to base engine by 34% and 48% respectively. The results of this experiment will be used for further improvement of the CNG-DI engine as well as to develop a new CNGDI car.